Main factors that cause negative complications of foot function after receiving mechanical traumatic injuries - Sokol , V. (Journal of Education, Health and Sport, 2021)
The article is devoted to an important and relevant area of ​​forensic and clinical research to clarify and implement in medical theory and practice the main factors that cause negative complications of lower extremity function after fractures and other injuries due to mechanical trauma during traffic accidents ( further - road accident) and lead to permanent disability of more than 33%. Therefore, the aim of the study was to identify the criteria that indicate the occurrence of severe consequences of mechanical injury in the form of permanent disability of more than 33%, and to determine the value of these prognostic criteria. The material of the study was 180 forensic examinations and tests and medical records of victims of road accidents. Of these, 120 examinations and research - the main group, and 60 - control. A number of current legal documents describing the concepts and types of disability have also been studied. The methods were scientific analysis of legal sources and methods of descriptive statistics of medical and forensic documentation. The results of the study allowed us to identify 8 groups of symptoms that cause the negative consequences of post-traumatic changes in the form of permanent disability of more than 33%. Based on the study of these signs, prognostic criteria for modern forensic assessment of the severity of injuries burdened with loss of general ability to work in the above range were developed. The ranking of these prognostic criteria in the main group (voters) was carried out. A number of clinical and forensic features of modern forms and types of mechanical trauma of the lower extremities during an accident and the consequences of such injuries have been identified. A number of inconsistencies of by-laws regulating forensic medical examination in the field of glossary on permanent disability are shown. Conclusions and recommendations for improving the theory and practice of forensic determination of the degree of disability are given.